2008
DOI: 10.1002/art.23334
|View full text |Cite
|
Sign up to set email alerts
|

A followup study of antiphospholipid antibodies and associated neuropsychiatric manifestations in 137 children with systemic lupus erythematosus

Abstract: Objective. To determine the prevalence of anticardiolipin antibodies (aCL), anti-␤ 2 -glycoprotein I (anti-␤ 2 GPI) antibodies, and lupus anticoagulant (LAC) in a large cohort of children with systemic lupus erythematosus (SLE), and to evaluate the associations with neuropsychiatric manifestations. Methods. A single-center retrospective cohort study with longitudinal followup of antiphospholipid antibodies (aPL) in 137 children with SLE (25 boys and 112 girls, mean age at diagnosis 13.0 years) was performed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 56 publications
3
60
1
19
Order By: Relevance
“…However, NLSLE pathogenesis is still controversial, and probably involve immune mediated as well as ischemic mechanisms. 16,17 In our patient, the old and new ischemic changes noted on MRI are consistent with an ischemic vascular process, but these can't be explained simply by the procoagulant effects of APL antibodies causing thrombotic occlusion of capillaries. It was hypothesized that an immune process may be responsible for a direct injury to the blood-brain barrier allowing autoantibodies to enter the nervous system and attack neurons involved in nigro-striatal pathways.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, NLSLE pathogenesis is still controversial, and probably involve immune mediated as well as ischemic mechanisms. 16,17 In our patient, the old and new ischemic changes noted on MRI are consistent with an ischemic vascular process, but these can't be explained simply by the procoagulant effects of APL antibodies causing thrombotic occlusion of capillaries. It was hypothesized that an immune process may be responsible for a direct injury to the blood-brain barrier allowing autoantibodies to enter the nervous system and attack neurons involved in nigro-striatal pathways.…”
Section: Discussionmentioning
confidence: 80%
“…It was hypothesized that an immune process may be responsible for a direct injury to the blood-brain barrier allowing autoantibodies to enter the nervous system and attack neurons involved in nigro-striatal pathways. [16][17][18][19] One meta-analysis showed that NPSLE patients have higher serum levels of certain antibodies including anticardiolipin, lupus anticoagulant, anti-ribosomal P, and antineuronal antibodies when compared with SLE patients who have no neurological involvement. 20 Other secondary factors that also contribute to the pathogenesis include infections associated with immunosuppressive treatments, hypertension, and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Lupic chorea is uncommon, being observed in 2% of cases of SLE 3 . As in rheumatic fever, it occurs in children aged around 11 years, especially females and it may be indistinguishable from Sydenham's chorea 3,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported APS as the primary cause of chorea 3,5,8 . It is rare manifestation and occurs especially in females.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 137 children with neuropsychiatric SLE, two children had transverse myelitis. Both tested positive for anticardiolipin antibodies and anti-b 2 glycosylphosphatidylinositol antibodies (1 was positive for lupus anticoagulant) (Avcin et al, 2008).…”
Section: Antiphospholipid Antibody Syndromementioning
confidence: 99%